2020
DOI: 10.21203/rs.3.rs-110596/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hand Washing Practice and Associated Factors among Primary School Children in Damot Woide Woreda of Wolaita Zone, South Ethiopia: A Cross-sectional study

Abstract: Background: Diarrhea and respiratory infections are respectively the leading causes of childhood mortality globally. Hand washing at schools with soap could substantially reduce diarrhea and respiratory infections among school-age children, however in developing countries it is still being practiced to a very low extent in particular critical moments such as before eating and after using sanitation facilities including toilet. Therefore, the main aim of this study was to determine the level of hand washing pra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
3
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(10 citation statements)
references
References 14 publications
6
3
1
Order By: Relevance
“…In our study, students' having a referent (role model) as parents, teachers, or health professionals for hand washing was significantly associated with hand washing practice, whereby students whose referents were parents were 4.41 times, teachers were 3.69 times and health professionals were 3.17 more likely to practice proper hand washing compared to friends. This finding is similar to the findings of other studies conducted in Ethiopia and Indonesia (19,20,31). This could be due to the close monitoring of students by health professionals, parents, and teachers as a result of the COVID-19 pandemic.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…In our study, students' having a referent (role model) as parents, teachers, or health professionals for hand washing was significantly associated with hand washing practice, whereby students whose referents were parents were 4.41 times, teachers were 3.69 times and health professionals were 3.17 more likely to practice proper hand washing compared to friends. This finding is similar to the findings of other studies conducted in Ethiopia and Indonesia (19,20,31). This could be due to the close monitoring of students by health professionals, parents, and teachers as a result of the COVID-19 pandemic.…”
Section: Discussionsupporting
confidence: 93%
“…The result from our study found that urban students were 3.5 times more likely to practice hand washing compared to students from rural residences. This was consistent with studies conducted in Ethiopia and Bangladesh (19,20,30) from urban residences were more likely to practice proper hand washing. This may be due to behavioral differences among rural and urban residents and also to inadequate provision of facilities like water and soap.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations